Made up : how the beauty industry manipulates consumers, preys on women's insecurities, and promotes unattainable beauty standards /: how the beauty industry manipulates consumers, preys on women's insecurities, and promotes unattainable beauty standards. (2020) - Laham, Martha
No abstract available